2014
DOI: 10.9790/0853-13614045
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation between Tympanoplasty Alone & Tympanoplasty Combined With Cortical Mastoidectomy in NonCholesteatomatous Chronic Suppurative Otitis Media in Patients with Sclerotic Bone

Abstract: Objectives: To compare the results of tympanoplasty alone and tympanoplasty with cortical mastoidectomy in chronic suppurative otitis media (CSOM) patients with sclerotic bone in terms of graft uptake, perforation closure, improvement in hearing and disease eradication. Study Design:Retrospective study of patients at tertiary referral hospital. Method: 50 cases of non-cholesteatomatous chronic suppurative otitis media were selected. Tympanoplasty alone was done in 25 cases and tympanoplasty combined with corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 17 publications
(17 reference statements)
4
22
0
Order By: Relevance
“…1 In the study conducted by Kaur et al, graft uptake was observed in 76% of cases undergoing myringoplasty. 20 In the study by Mishiro et al, graft success rates were 93.3% in group of tympanoplasty. 22 Balyan et al in the study observed that successful graft uptake was seen in 89.2% cases undergoing myringoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the study conducted by Kaur et al, graft uptake was observed in 76% of cases undergoing myringoplasty. 20 In the study by Mishiro et al, graft success rates were 93.3% in group of tympanoplasty. 22 Balyan et al in the study observed that successful graft uptake was seen in 89.2% cases undergoing myringoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] Traditionally it has been a common belief that tympanoplasty should be done in a totally dry ear to obtain a successful surgery, but slowly surgeons have started performing tympanoplasty alone even for quiescent and of late even for wet ears.…”
Section: Discussionmentioning
confidence: 99%
“…10 Many other studies as well have opined that role of cortical mastoidectomy in non-cholesteatomatous CSOM is statistically insignificant. [11][12][13][14][15][16] Though most of the studies have shown no evidence of improved outcomes following mastoidectomy compared to tympanoplasty alone when reviewed by Eliades et al, subgroup analysis, including actively discharging ears, extensive mucosal inflammation, large or repeat perforations, or sclerotic mastoids have had overall worse outcomes and these patients have shown a nonsignificant trend towards slightly improved results with mastoidectomy. 17 Hence in this study we intend to study the factors influencing decision making among ENT surgeons on whether or not to perform cortical mastoidectomy as an adjunct to tympanoplasty in patients with CSOM-tubotympanic disease with wet or quiescent ears.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations